Are dietetics educators' attitudes to assessment a barrier to expanding placement opportunities? Results of a Delphi study. Issue 3 (18th June 2015) - Palermo, Claire; Capra, Sandra; Beck, Eleanor J.; Ash, Susan; Jolly, Brian; Truby, Helen
Abstract: Aim: Assessment of entry‐level health professionals is complex, especially in the work‐based setting, placing additional pressures on these learning environments. The present study aims to gain understanding and ideally consensus regarding the setting for assessment of all elements of competence for entry‐level dietitians across Australia. Methods: Seventy‐five experienced academic and practitioner assessors were invited to participate in an online Delphi survey. The 166 entry‐level performance criteria of the competency standards for dietitians formed the basis of the questions in the survey, with rating on which ones could be assessed in the practice setting, those which could be assessed in a classroom/university setting and which could be assessed in either setting. Forty‐three of 75 invited assessors responded to the first round of the Delphi. A second modified survey was sent to the 43 participants with 34 responding. Results: Consensus was achieved for the assessment setting for 86 (52%) of the performance criteria after two rounds of surveying. The majority of these performance criteria achieved consensus at round one (n = 44) and were deemed to be best assessed in the practice setting (n = 55). This study highlighted the perspectives of assessors and their preference for the work‐based setting for assessment. Conclusions: To reduce the focus on work‐based settings as the only place for competence‐based assessment of health professionals, there is a need to support individual and organisational change through challenging existing norms around assessment.